Compressive and Impact Loads’ Effects on The Behaviour of SIFCON Made of Plastic Waste Fibers - Al-Hadithi, Anas; Al-Hadithi, Abdulkader (Iraqi Journal of Civil Engineering, 2022)
SIFCON is a relatively new material and consists of slurry (cement or cement and sand), water, super plasticizers (water reducers) and fibers. In all previous research, steel fibers and other types of fibers were used, but in this study, waste plastic fibers Polyethylene Terephthalate (PET) created by cutting carbonated beverage bottles were used for the first time in the production of SIFCON. Three volume ratios (3%, 6% and 10%) of the total volume of the concrete mixture were used to add fibers in different volume ratios, and a reference concrete mixture was created for comparison. Tests of compressive strength, impact resistance, ultrasound transmission velocity check and other tests were performed on the constructed models. Compared with the reference concrete, according to the analysis of the results. The results showed an improvement in the compressive strength it increased by (18.5%), an increase in the impact resistance by (416.67%), and a decrease in the velocity of ultrasound by (19.42%).